2018
DOI: 10.3390/rs10071082
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Biomass and Nitrogen Amount of Barley and Grass Using UAV and Aircraft Based Spectral and Photogrammetric 3D Features

Abstract: Abstract:The timely estimation of crop biomass and nitrogen content is a crucial step in various tasks in precision agriculture, for example in fertilization optimization. Remote sensing using drones and aircrafts offers a feasible tool to carry out this task. Our objective was to develop and assess a methodology for crop biomass and nitrogen estimation, integrating spectral and 3D features that can be extracted using airborne miniaturized multispectral, hyperspectral and colour (RGB) cameras. We used the Rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
126
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 132 publications
(132 citation statements)
references
References 75 publications
6
126
0
Order By: Relevance
“…We tested whether the combination of different types of data resulted in a better DMY prediction and investigated the influence of the methodology selected for the regression. As demonstrated by Bendig et al () and Brocks and Bareth () for barley, Yue et al () for winter wheat, Näsi et al () for a timothy and meadow fescue mixture or for maize in Geipel et al (), and as is shown in our regression analysis, the canopy height is (well) correlated to yield. Slightly lower correlation values ( r = .79) were obtained in comparison with those reported by Viljanen et al () for a timothy and meadow fescue mixture ( r ranges from .79 to .98).…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…We tested whether the combination of different types of data resulted in a better DMY prediction and investigated the influence of the methodology selected for the regression. As demonstrated by Bendig et al () and Brocks and Bareth () for barley, Yue et al () for winter wheat, Näsi et al () for a timothy and meadow fescue mixture or for maize in Geipel et al (), and as is shown in our regression analysis, the canopy height is (well) correlated to yield. Slightly lower correlation values ( r = .79) were obtained in comparison with those reported by Viljanen et al () for a timothy and meadow fescue mixture ( r ranges from .79 to .98).…”
Section: Discussionsupporting
confidence: 89%
“…for barley,Yue et al (2017) for winter wheat,Näsi et al (2018) for a timothy and meadow fescue mixture or for maize inGeipel et al (2014), and as is shown in our regression analysis, the canopy height is (well) correlated to yield. Slightly lower correlation values(r = .79) were obtained in comparison with those reported by Viljanen et al…”
supporting
confidence: 81%
See 3 more Smart Citations